2014
DOI: 10.2215/cjn.08350813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pravastatin on Total Kidney Volume, Left Ventricular Mass Index, and Microalbuminuria in Pediatric Autosomal Dominant Polycystic Kidney Disease

Abstract: Background and objectives In autosomal dominant polycystic kidney disease (ADPKD), progressive kidney cyst formation commonly leads to ESRD. Because important manifestations of ADPKD may be evident in childhood, early intervention may have the largest effect on long-term outcome. Statins are known to slow progressive nephropathy in animal models of ADPKD. This randomized double-blind placebo-controlled phase III clinical trial was conducted from 2007 to 2012 to assess the effect of pravastatin on height-correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 51 publications
(51 reference statements)
0
101
0
3
Order By: Relevance
“…Likewise, somatostatin (octreotide) and the mammalian target of rapamycin (mTOR) inhibitor rapamycin have been used, but with limited or disappointing results, and are also excessively expensive. [20,23] Cadnapaphornchai et al [24] recently reported on the prevention of a reduction in kidney volume and cyst growth, which was accom panied by kidney functional stability, using pravastatin in children and adults, with striking results. The use of statins is not new and both experimental and clinical mechanisms of renal protection in ADPKD have previously been shown.…”
Section: Autosomal-dominant Polycystic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, somatostatin (octreotide) and the mammalian target of rapamycin (mTOR) inhibitor rapamycin have been used, but with limited or disappointing results, and are also excessively expensive. [20,23] Cadnapaphornchai et al [24] recently reported on the prevention of a reduction in kidney volume and cyst growth, which was accom panied by kidney functional stability, using pravastatin in children and adults, with striking results. The use of statins is not new and both experimental and clinical mechanisms of renal protection in ADPKD have previously been shown.…”
Section: Autosomal-dominant Polycystic Kidney Diseasementioning
confidence: 99%
“…In addition, statins inhibit angiogenesis. [24] It would be interesting to investigate whether the production of glycogen synthase kinase-3β (GSK3β) is altered. GSK3β has recently been shown to play a role in ADPKD via induction of proliferation of cystic epithelial cells.…”
Section: Autosomal-dominant Polycystic Kidney Diseasementioning
confidence: 99%
“…26 The randomized double-blind placebo-controlled trial conducted with 110 children with ADPKD and normal kidney function studied the effect of pravastatin on the progression of disease. 27 All patients had lisinopril treatment. They were randomized to treatment with pravastatin or placebo.…”
Section: Statin Usementioning
confidence: 99%
“…The number of patients reaching end point for TKV was significantly lower in the pravastatin group. 27 …”
Section: Statin Usementioning
confidence: 99%
“…This issue of CJASN also includes the first published randomized placebo-controlled clinical trial of deliberate statin use to evaluate potential benefit on height-corrected TKV change of ADPKD in children and young adults (43). This trial evaluated either 20 or 40 mg pravastatin combined with an angiotensin-converting enzyme inhibitor in young patients aged 8-22 years with ADPKD.…”
Section: Statinsmentioning
confidence: 99%